2015
DOI: 10.1007/s11906-015-0576-7
|View full text |Cite
|
Sign up to set email alerts
|

Preeclampsia: What Does the Father Have to Do with It?

Abstract: Preeclampsia (PE) is one of the leading causes of maternal and fetal morbidity and mortality, with incidence rates ranging between 2 and 5 % in the Western World. The exact causes of the disease remain largely unknown, because of the complex pathophysiologic mechanisms involved in the process. Genetic, environmental, and epigenetic parameters have been implicated by various authors as culprits for the pathogenesis of PE. Recent reports in the literature highlight the paternal role. Still, the exact extent and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 30 publications
1
10
0
Order By: Relevance
“…Importantly, this association may be determined by the genotype of the child, not the genotype of the mother. These observations are consistent with the known paternal influence on preeclampsia, 57 since APOL1 allele contributions from each parent appear necessary to predispose the mother to an at-risk pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…Importantly, this association may be determined by the genotype of the child, not the genotype of the mother. These observations are consistent with the known paternal influence on preeclampsia, 57 since APOL1 allele contributions from each parent appear necessary to predispose the mother to an at-risk pregnancy.…”
Section: Discussionsupporting
confidence: 86%
“…The less favorable outcome for female only carriers or homozygotes versus males also suggests that the maternal contribution is not confined to the transmission of the M2 haplotype to the fetus and needs further elucidation. There is growing evidence that male factors are important for abnormal placentation and the development of PE (Κatsi et al, 2015). The association shown in this study of the paternal ANXA5 M2 haplotype with adverse outcomes adds weight to the hypothesis that male factors play also play a role in PMPC.…”
Section: Discussionmentioning
confidence: 99%
“…47 The only meta-analyses exploring paternal factors investigated the contribution of anti-paternal human leucocyte antibodies (HLA) and suggested that human leukocyte antigen G (HLA-G) expressed on the invading cytotrophoblast is important for the maternal adaptation of the placental vessels. 48 A shorter duration of exposure to seminal fluid is responsible for an increased risk of developing pre-eclampsia. 47 This is also demonstrated by an escalated risk of pre-eclampsia in pregnancies conceived as a result of ovum donation in azoospermic partners and after a short duration or a single act of unprotected intercourse.…”
Section: Paternal Mental Healthmentioning
confidence: 99%
“…54 Furthermore, studies on paternal family history of genetic thrombophilia, hypertension, and cardiovascular disease reflect genes passed through the feto-placental unit via the father, which are associated with a number of adverse pregnancy outcomes. 48 This may be through single-nucleotide polymorphisms in the paternally expressed insulin-like growth factor (IGF2), which is responsible for trophoblastic invasion and placental function. 48 Likewise, there are several other possible pathways by which certain viruses, such as cytomegalovirus (CMV) and herpes virus, bacterial, fungal, and parasitic infections, have the potential to contribute to adverse pregnancy outcomes and, more specifically, to pre-eclampsia.…”
Section: Paternal Mental Healthmentioning
confidence: 99%